2019
DOI: 10.1007/s00521-019-04231-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and deep learning clusters based on neural networks for management decision structures

Abstract: Judgments are taken in a structured way; both human and business management decisions involve a hierarchical process that requires a level of compromise between risk, cost, reward, experience and knowledge. This article proposes a management decision structure that emulates the human brain approach based on genetic and deep learning cluster algorithms and the random neural network. Reinforcement learning takes quick and specific local decisions, deep learning clusters enables identity and memory, and deep lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…This allows the classifier to identify when a test example could represent a novel class, or a new regime in the domain time series forecasting (Liu & Zhang, 2010). It is demonstrated that their related cost function is local minima free with respect to all the network weights (Serrano, 2019).…”
Section: Radial Basis Function Networkmentioning
confidence: 99%
“…This allows the classifier to identify when a test example could represent a novel class, or a new regime in the domain time series forecasting (Liu & Zhang, 2010). It is demonstrated that their related cost function is local minima free with respect to all the network weights (Serrano, 2019).…”
Section: Radial Basis Function Networkmentioning
confidence: 99%
“…However, these approaches relied on full information with model-free learning with uncertainty [82]. Management decision support was explored in model-free case studies in investment applications [83]. Due to the complexity of its learning, the application is limited to laboratory case studies [84].…”
Section: Smart Production Controlmentioning
confidence: 99%
“…Reinforcement learning is used for fast and quick decisions in unsupervised scenarios; deep learning clusters based on gradient descent are most suited for identity and memory, although they are computationally expensive; and finally, genetic algorithms transmit information to future generations [21]. In addition, artificial intelligence has been used to make management decisions in complex management structures [22].…”
Section: Infrastructures 2019 4 52 3 Of 24mentioning
confidence: 99%